EDUKASI DAN PEMBERDAYAAN KELOMPOK TANI SAWIT KABUPATEN DHARMASRAYA MELALUI PEMANFAATAN KUMBANG ELAEIDOBIUS KAMERUNICUS UNTUK MENINGKATKAN PRODUKTIVITAS DAN KESEJAHTERAAN MASYARAKAT - Martinsyah, Rachmad Hersi; Ramadhan, Nugraha; Obel, Obel; Rezki, Dewi; Suhendra, Dede; Jannatan, Robby; Ronaldi, Ronaldi; Siswandra, Diko Okta; Diansyah, Rohan (Jurnal Abdi Insani, 2025)
This community service activity aimed to enhance the knowledge, skills, and awareness of oil palm farmers regarding the crucial role of the pollinating weevil Elaeidobius kamerunicus in supporting the natural and sustainable increase of oil palm fruit productivity. Currently, the low productivity of smallholder oil palm farms is generally caused by suboptimal pollination processes, a lack of farmer understanding of the biology and life cycle of pollinating insects, and the limited application of environmentally friendly technologies. The implementation methods of this service included counseling, interactive discussions, and field demonstrations on the identification, conservation, and utilization strategies of E. kamerunicus in oil palm plantations. The activity results showed an increase in farmer knowledge by 76.92% (based on pre-test and post-test), improved farmer skills in recognizing and preserving the habitat of the pollinating weevil, and the growth of collective awareness to reduce the use of pesticides that potentially harm pollinator insect populations. The long-term impact of this program is expected to increase oil palm fruit productivity, strengthen the economic resilience of farmers, and support the realization of more environmentally friendly and sustainable oil palm cultivation practices. Thus, this education and empowerment activity makes a real contribution to improving the welfare of oil palm farming communities while preserving the plantation agroecosystem.